A Multi-Party Imaginary Dialogue about Power and Cybernetics - Phillip Guddemi (Integral Review, 2010)
This paper is written as a multi-sided dialogue intended to present a number of ideas about power. Some of these ideas are my own, expressed in a kind of evolutionary idiom of adaptation though they were partly developed in reaction to Foucault (and are far more indebted to Foucault and cybernetics than to contemporary evolutionist thinking). There is a deep irony in that my way of thinking is primarily rooted in the cybernetic anthropology of Gregory Bateson; however, he was deeply skeptical of the concept of power. My personification of him in this dialogue, as “Bateson,” demonstrates this skepticism and brings into the discussion other relevant ideas of his. The third participant in the dialogue, Mary Midgley, is included because her consideration of Hobbes’ ideas leads us to consider yet another, probabilistic, way of thinking about power.